Ritual as a source of conflict - Langer, Robert (Ritual, media, and conflict, 2011)
This chapter assembles four cases and asks: under what conditions do publicly mediatized rituals and ritualized practices become a source of conflict? In the first case, the authors show that when Freemasons, using pamphlets as their medium, exposed imprecations in a ritual oath, conflict emerged, because sovereignty was a privilege that European states and churches regarded as their own exclusive prerogative. The second case argues that when the Muslim call to prayer is performed in public space by immigrants in present-day European countries, and when the media report on these actions, local discussions about participation are transformed into national debates about cultural space. The third example traces the shifting identity boundaries created in contemporary Turkey by the display of Alevi rituals in the media. The final case, that of the educational practices of American evangelicals, as depicted in the film, Jesus Camp, examines mediatized attempts to gain political influence in the United States.